Penggunaan Metode PQ4R dalam Meningkatkan Prestasi Belajar Siswa Kelas VII SMPN 1 Kandanghaur Indramayu - Sahrudin Sahrudin (IAIN Ternate, 2021)
The purpose of this study was to findout and obtain information about: Islamic Religious Education Learning in Class VIISMP Negeri 1 KandanghaurIndramayu Regency before the PQ4R method was applied(preview, question, read, reflect, recite and review), the efforts of Islamic ReligiousEducation teachers in applying the method PQ4R (preview, question, read, reflect, reciteand review) in Class VII SMP Negeri 1 Kandanghaur, Indramayu Regency, and theresults of applying the PQ4R method (preview, question, read, reflect, recite and review)in Class VII SMP Negeri 1 Kandanghaur Regency Indramayu in improving studentachievement. For the continuation of this research, the author will refer to the principlesof applying descriptive methods, supported by observation techniques, interviews,documentation studies and questionnaires as data collection tools.The collected datawas then analyzed using inductive data analysis.